Imfihlo - Siwani, Buhlebezwe (Michaelis School of Fine Art, 2016)
The discourses of ritual, culture and ethics has, over the years, been a primarily ethnographic, philosophical and dramaturgical concern. Secrecy seems central in setting boundaries. Using ritual and culture as the common thread, I question the boundaries that are transgressed by contemporary South African artists in 'showing' and 'telling' things that are otherwise considered as secret. I discuss the ways in which my own practice as an artist and isangoma troubles the threshold. Considering the ideological function of the secret, my work examines the power relations implied in both keeping and divulging 'secrets'. This research poses the question: how does the performance or re-enactment of the secret elements of cultural and traditional practice in live, performance and installation art complicate cultural ethics? Through a discussion of my work, Imfihlo, as well as works by artists such as Nicholas Hlobo, Pieter Hugo, Churchill Madikida, Nelisiwe Xaba and Mocke J van Veuren, I relate the role of secrecy in ideological structures with the trace. This concept exists throughout my research, whether it be in: forgotten histories; rituals and people (what the artist leaves behind); tracing space, or; by exploring the trace as an existential body, a trace of someone who once was, who exists in another realm, and many traces in one body.